OBSERVED SHIFT AND MERGE OF HYDROLOGICAL REGIMES IN THE SOTA CATCHMENT, BENIN; AN EVIDENCE OF CLIMATE CHANGE - G. T., Oyerinde; B.T., Olowookere (International Journal of Research -GRANTHAALAYAH, 2018)
Sub-Saharan Africa have low resilience capacities to the challenges of climate change. This study is aimed at assessing climate trends and regime shifts at the Sota Catchment, Benin. Long term rainfall and river discharge were analyzed from 1950-2010 in order to generate patterns of changes in the basin. Analysis of the hydro-meteorological were based on the two prominent vegetation zones (Sudan and Guinea Savannah) in the catchment. The rainfall and discharge data were subjected to regime shift analysis and Standardized Precipitation Indices (SPI) were computed. Downward trend of precipitation was observed in the Guinea and Sudan vegetation zones of the catchments from 1970. Rainfall and runoff amount at the two assessed vegetation zones was different in the Guinea and Sudan zone up till 1970. Clear merge of rainfall and runoff amount and patterns was witnessed between the two vegetation zones at 2007. This calls for attention of scientists and policy makers in the region to deploy necessary adaptation measures based on such clear evidence of climate change.